Development and Analysis of Arrow for Archery - Wong, Fei Yong; Zulkifli, Ahmad@Manap; Idris, Mat Sahat (2015)
This project is about the development and analysis of arrow for archery. 3 types of arrow head been designed: bullet shaped head, 3D shaped head and cone shaped head. The arrow performance measurement parameters were studied such as the FOC values, static stiffness values and the drag forces. SolidWorks 2012 was used to designs the three types of arrow head and the drag force is simulated by using SolidWork Flow Simulation. The material used for the arrow head fabrication is stainless steel 304. The arrow shafts used are carbon shaft of 5.46mm outer diameter and 7mm fiberglass and carbon fiber shaft. 3 different shaft properties are used to determine the effect of static stiffness, arrow heads weight and shaft diameter on the drag force generated at the arrow. The experimented result for Beman 570-14 arrows are slightly higher compared to simulation results obtained from SolidWorks. The possible cause is the characteristic of the arrow during flight where arrows starts to bend in C manner then straight again then bend again in reverse C manner and so on when it been shot. These deformation causes energy losses to the surrounding due to air friction, natural damping effect and shear friction. From the result obtained, it is shown that fiberglass shaft arrow has the highest drag force regardless of the arrow head types used compared to the other two types of shaft. Although Beman 570-14 shaft has smaller frontal area compared to a 7mm outer diameter carbon fiber shaft, the drag force obtained from the experiment shows that both bullet shaped head and 3D shaped head for carbon fiber shaft has lower drag force compared with the same arrow head shape.